Partisipasi Masyarakat Terhadap Pengelolaan Sampah di Kelurahan Bangetayu Wetan Kecamatan Genuk Kota Semarang - Prayitno, M Windi Setyo (Indonesian Journal of Geography Education; Vol 1 No 1 (2020): Indonesian Journal of Geography Education, 2020)
This research is motivated by still limited information about the type of waste management in the Bangetayu Wetan Village, so that people tend to manage waste in a haphazard or modest manner. The purpose of the study are to analyze the ways of the community of Bangetayu Wetan village in managing waste in daily activities and the level of community awareness in good and efficient waste management so that they are able to explore the economic side of waste management. These research is done by qualitative methods through stages such as observation and interviews. The results showed: 1) waste management carried out by most of the community is still traditional. This means that the community is focused on the activities of disposing or distributing to Temporary Disposal Sites (TPS). 2) the community has participated in waste management activities in every stage such as planning, disposing and distributing, and mutual cooperation in cleaning the environment.